# Samacheer Kalvi 9th Maths Solutions Chapter 3 Algebra Ex 3.5

You can Download Samacheer Kalvi 9th Maths Book Solutions Guide Pdf, Tamilnadu State Board help you to revise the complete Syllabus and score more marks in your examinations.

## Tamilnadu Samacheer Kalvi 9th Maths Solutions Chapter 3 Algebra Ex 3.5

9th Class Math Exercise 3.5 Solution Question 1.
Factorise the following expressions:
(i) 2a2 + 4a2b + 8a2c
(ii) ab – ac – mb + mc
Solution:
(i) 2a2 + 4a2b + 8a2c = 2a2 [ 1 + 2b + 4c]
(ii) ab – ac – mb + mc = a(b – c) – m (b – c) = (b – c) (a – m)

9th Maths Exercise 3.5 Question 2.
Factorise the following:
(i) x2 + 4x + 4
(ii) 3a2 – 24ab + 48b2
(iii) x5 – 16x
(iv) $$m^{2}+\frac{1}{m^{2}}$$ – 23
(v) 6 – 216x2
(vi) $$a^{2}+\frac{1}{a^{2}}$$ – 18
Solution:
(i) x2 + 4x + 4 = (x + 2) (x + 2) = (x + 2)2
∵ (a + b)2 = a2 + 2ab + b2
(ii) 3a2 – 24ab + 48b2 = 3[a2 – 8ab + 16 b2]
= 3 [a – 4b]2 (∵ (a – b)2 = a2 – 2ab + b2)
(iii) x5 – 16x = x[x4 – 16] = x [(x2)2 – 42]
= x (x2 + 4) (x2 – 4)= x (x2 + 4) (x + 2) (x – 2)

Class 9 Maths Exercise 3.5 Solutions Question 3.
Factorise the following:
(i) 4x2 + 9y2 + 25z2 + 12xy + 30yz + 20xz
(ii) 25x2 + 4y2 + 9z2 – 20xy + 12yz – 30xz
Solution:
(i) 4x2 + 9y2 + 25z2 + 12 xy + 30 yz + 20 xz
= (2x)2 + (3y)2 + (5z)2 + 2 (2x) (3y) + 2 (3y) + (5z) + 2 × 3y × 5z
= (2x + 3y + 5z)2
∵ (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca

(ii) 25x2 + 4y2 + 9z2 – 20xy + 12 yz – 30xz
= (5x)2 + (-2y)2 + (-3z)2 + 2(5x) (-2y) + 2 (-2y) (-3z) + 2 (-3z) (5x)
= (5x – 2y – 3z)2

Exercise 3.5 Class 9 Question 4.
Factorise the following
(i) 8x3 + 125y3
(ii) 27x3 – 8y3
(iii) a6 – 64
Solution:
(i) 8x3 + 125y3 (2x)3 + (5y)3
∴ a3 – b3 = (a + b) (a2 – ab + b2)
= (2x + 5y) [(2x)2 – (2x)(5y) + (5y2]
= (2x + 5y )2 (4x2 – 10xy + 25y2)

(ii) 27x3 – 8y3 = (3x)3 – (2y)2
= (3x – 2y ) ((3x)2 + 3x × 2y + (2y)3)
= (3x- 2y) (9x3 + 6xy + 4xy + 4y3)

(iii) a6 – 64 = (a2)3 – 43 (a3 – b3 = (a – b) (a2 + ab + b2)
= (a2 – 4) (a4 + 4a2 + 42)
= (a + 2) (a – 2) (a2 + 4 – 2a) (a2 – 4 + 2a)

9th Maths Algebra Exercise 3.5 Question 5.
Factorise the following:
(i) x3 + 8y3 + 6xy – 1
(ii) l3 – 8m3 – 27n3 – 18lmn
Solution:
(i) x3 + 8y3 + 6xy – 1 = x3 + (2y)3 + (-1)3 – 3 (x) (2y) (-1)
= (x + 2y – 1) (x2 + 4y2 + 1 – 2xy + 2y + x)

(ii) l3 – 8m3 – 27n3 – 18lmn = l3 + (-2m)3+ (-3n)3 -3 (l) {-2m) (-3n)
= (l – 2m – 3n) (l2 + (-2m)2 + (-3n)3 – l × – 2m – (-2m × -3n) – (-3n × l))
= (l – 2m – 3n) (l2 + 4m2 + 9n2 + 2lm – 6mn + 3nl)